A proposal for developing a fashion illustration manual - Rangel, John Paul S.; Elumba, Ma. Patricia S. (2004.)
The study proposes the development of a fashion illustration manual. This study should be useful to all fashion design students, practitioners and specialists. It reviewed selected materials on fashion illustration to determine the fundamentals of the activity. This study proposes a fashion illustration method or technique that attempts to make fashion illustration easier to do. A review of related materials on fashion illustration was done to study the techniques, concepts, exercises and applications. The data gathered from the review of materials were evaluated for ease and efficiency. The techniques, concepts, exercises and applications that were studied for the proposal for a fashion illustration manual were collated and compared to identify the fundamentals that can be part of this manual. This study tried to determine the criteria for a fashion illustration manual which can be used by design students, fashion practitioners and clothing specialists with greater ease and simplicity in approach.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Fashion drawing -- Handbooks, manuals, etc